2022
DOI: 10.1039/d1ew00659b
|View full text |Cite
|
Sign up to set email alerts
|

Potential for colloid removal from petrochemical secondary effluent by coagulation–flocculation coupled with persulfate process

Abstract: The selective removal characterization of colloids in petrochemical secondary effluent treated by coagulation-flocculation (CF) coupled with persulfate (PS) process was investigated. Results showed that the optimal dosages for CF-PS were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…When PS is used alone, the removal rates of 3–50 kDa and DOC lower than 3 kDa are 62.7% and 40.3%, respectively. CF pretreatment enhances the removal of medium- and high-molecular-weight lysine and tryptophan, and PS can remove humic organics and extracellular polymers more thoroughly [ 43 ]. Zhou et al reported a new strategy of using Ag/TiO 2 /GO as AOP catalysts and PVDF for synergistic removal, efficiently inactivating low-concentration ARGs in target wastewater through interfacial adsorption and oxidation degradation [ 133 ].…”
Section: Contribution Of Pretreatment Scheme For Ep Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…When PS is used alone, the removal rates of 3–50 kDa and DOC lower than 3 kDa are 62.7% and 40.3%, respectively. CF pretreatment enhances the removal of medium- and high-molecular-weight lysine and tryptophan, and PS can remove humic organics and extracellular polymers more thoroughly [ 43 ]. Zhou et al reported a new strategy of using Ag/TiO 2 /GO as AOP catalysts and PVDF for synergistic removal, efficiently inactivating low-concentration ARGs in target wastewater through interfacial adsorption and oxidation degradation [ 133 ].…”
Section: Contribution Of Pretreatment Scheme For Ep Removalmentioning
confidence: 99%
“…Multi-unit filtration is considered to be one of the strategies that is able to effectively improve the membrane separation effect [ 39 , 40 , 41 , 42 ]. The corresponding screening effect of different size ranges on molecular weight can also be used to calculate the molecular weight distribution of organic substances [ 43 , 44 ]. The removal effect of ARGs mainly depends on the pore size of the membrane [ 45 ], and compared with spiral and round DNA molecules, linear molecules with similar molecular weight often have more appropriate escape ability [ 22 ].…”
Section: Introductionmentioning
confidence: 99%